2003
DOI: 10.1128/aac.47.4.1324-1333.2003
|View full text |Cite
|
Sign up to set email alerts
|

Activities of Atazanavir (BMS-232632) against a Large Panel of Human Immunodeficiency Virus Type 1 Clinical Isolates Resistant to One or More Approved Protease Inhibitors

Abstract: To evaluate the cross-resistance profile of the human immunodeficiency virus type 1 protease inhibitor (PI) atazanavir (BMS-232632), a panel of 551 clinical isolates exhibiting a wide array of PI resistance profiles and a variety of genotypic patterns were assayed for susceptibility to atazanavir and six other PIs: amprenavir, indinavir, lopinavir, nelfinavir, ritonavir, and saquinavir. In general, reductions in atazanavir susceptibility in vitro required several amino acid changes and were relatively modest i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
66
0
2

Year Published

2004
2004
2013
2013

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 89 publications
(70 citation statements)
references
References 33 publications
(33 reference statements)
2
66
0
2
Order By: Relevance
“…1 As measure of potency, the concentration that inhibits 50% of viral replication (IC50) in the absence of human serum ranged from 0.58 ng/mL to 5.7 ng/mL in a panel of susceptible viruses isolated from 31 PI-naïve HIV-infected patients. 2,3 The presence of 40% human serum in cell cultures increased ATV IC50 by 2.7-to 3.6-fold, as noticed for other PIs. The adjusted IC50 for protein binding was estimated to range from 8 to 20 ng/mL against reference viral strains with a conventional cycle cell infection and the PhenoSense TM single assay (ViroLogic Inc., South San Francisco, CA, USA), respectively.…”
Section: Mechanism Of Actionsupporting
confidence: 55%
See 2 more Smart Citations
“…1 As measure of potency, the concentration that inhibits 50% of viral replication (IC50) in the absence of human serum ranged from 0.58 ng/mL to 5.7 ng/mL in a panel of susceptible viruses isolated from 31 PI-naïve HIV-infected patients. 2,3 The presence of 40% human serum in cell cultures increased ATV IC50 by 2.7-to 3.6-fold, as noticed for other PIs. The adjusted IC50 for protein binding was estimated to range from 8 to 20 ng/mL against reference viral strains with a conventional cycle cell infection and the PhenoSense TM single assay (ViroLogic Inc., South San Francisco, CA, USA), respectively.…”
Section: Mechanism Of Actionsupporting
confidence: 55%
“…In vitro analysis of the genotypic profi les of 943 PI-susceptible and PI-resistant clinical isolates identifi ed a strong correlation between the presence of several amino acid changes at specifi c residues (10I/V/F, 20R/M/I, 24I, 33I/F/V, 36I/L/V, 46I/L, 48V, 54V/L, 63P, 71V/T/I, 73C/S/T/A, 82A/F/S/T, 84V, and 90M) and decreased susceptibility to ATV. 2 In addition, data from PI-experienced patients revealed that the median number of PI-associated resistance mutations was lower in patients showing virological response than in non-responders. 9 As with other PIs, failure of ATV is often rather better explained by lack of potency than by the acquisition of primary resistance mutations, especially in patients without previous PI failure.…”
Section: Drug Resistancementioning
confidence: 99%
See 1 more Smart Citation
“…Earlier in vitro studies demonstrated that the substitutions M46I, A71V, N88S, I84V, and I50L, which were identified in laboratory strains of PRT variants selected against atazanavir, may play important roles in the resistance phenotype and that multiple mutational pathways can lead to resistance (17). In clinical studies of treatment-experienced patients who received atazanavir-containing regimens, a reduction in atazanavir susceptibility required combinations of several amino acid substitutions (7). High levels of atazanavir resistance were observed only with HIV isolates cross-resistant to all approved PIs, and these viruses were characterized by the accumulation of several mutations (M46I, I84V, N88S/D, and L90M).…”
mentioning
confidence: 99%
“…The loss of PRT susceptibility of viral isolates with the IRM mutations to the approved PIs, atazanavir included, varied between 7-and 71-fold (17). The M46I and L90M substitutions were associated with atazanavir resistance in clinical studies (7). Furthermore, the V82F and I84V subset, especially when present in tandem, has been shown to adversely affect PRT susceptibility (17,23,55).…”
mentioning
confidence: 99%